Method and theory in the study of Islamic origins - Berg, Herbert 19XX- (Islamic history and civilization. Studies and texts 0929-2403, 2003)
Literary scholars and Arabists from Europe, Israel, and the US set out their various, divergent, and often mutually exclusive theories about how Islam began. The dozen studies, all but one written for the anthology, are arranged in sections according to their primary source and focus: history and Sirah, Sunnah and Hadith, Qur'an and Tafsir, and